Low ON-Resistance GaN Schottky Barrier Diode With High VON Uniformity Using LPCVD Si3N4 Compatible Self-Terminated, Low Damage Anode Recess Technology - Gao, Jingnan; Jin, Yufeng; Xie, Bing; Wen, C.P.; Hao, Yilong; Shen, Bo; Wang, Maojun (IEEE Electron Device Letters, 2018)
In this letter, we demonstrate a recessed-anode Schottky barrier diode (SBD) on a double AlGaN/GaN heterojunction structure. A self-terminated, oxidation/wet etching with low-pressure chemical vapor deposition (LPCVD) Si3N4 mask is applied in the anode recess process. Unlike common plasma-based, dry etching techniques, the etched surface is not subjected to ion bombardment, and the etch depth is precisely controlled. As a result, a high effective channel mobility of 1079 cm2/V . s is maintained in the channel beneath the recess surface. The fabricated devices with a 15-mum anode-to-cathode distance (LAC) are found to exhibit a uniform, low turn-ON voltage (VON) of 0.69 +or- 0.03 V, and a low specific on-resistance (RON,SP) of 2.83 mQ . cm2. The SBDs also show excellent off-state blocking characteristics due to the smooth recess interface together with the assistance of LPCVD grown Si3N4. A breakdown voltage of 1190 V is achieved for the SBDs with 15-mum LAC at a leakage current criteria of 1 muA/mm, and the Baliga's figure-of-merit is 500 MW/cm2.